PENDAMPINGAN HARMONISASI PERATURAN PERPAJAKAN UU NO. 7 TAHUN 2021 PADA GRUP PT. SAHABAT AGRO MAKMUR SEJAHTERA MAKASSAR - Ng, Suwandi; E. Daromes, Fransiskus (Universitas katolik Musi Charitas, 2024)
Law No. 7 of 2021 regulates the subject matter of General Provisions and Tax Procedures, namely Harmonization of Tax Regulations (HPP). The reasons behind the creation of the HPP Law aim to increase sustainable economic growth, support the acceleration of economic recovery, optimize state revenues, create a tax system that is fairer, provide legal certainty, and implement administrative reform and harmonious and consolidative tax policies. However, changes to several important components in the HPP Law have an impact on the mechanisms and technical calculations of tax components, especially operational technical ones. This service activity is designed to socialize, provide assistance, and provide simulations for companies and taxpayers. The expected output from this service is a real understanding from taxpayers.